Usage of ChatGPT and SciSpace in Research Ideation and Literature Review: A Viewpoint - Yusra Nasir (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2024)
In recent times, academic researchers have incorporated the latest techniques to amplify their traditional research tasks to be more innovative. ChatGPT and Scispace, have gained rapid popularity among academics from brainstorming ideas, conducting literature reviews, data analysis, and manuscript write up. These available AI tools help assist researchers by quickly identifying relevant studies, summarize findings, and organize information in multiple columns1,2. AI tools have the potential to systematize repetitive and time-consuming tasks, such as data collection, literature searches, and formatting references. This lets the researchers focus on more complex and creativen aspects of their research work1. This viewpoint shares the experiences based on a workshop conducted for Physiotherapy faculty to sensitize them with hands-on demonstration of AI tools along with the practical benefits and limitations.